THE URGENCY OF TB DIAGNOSIS AT THE PRESENT STAGE - Bilash, S.; Ilchenko, V.; Voroduhina, A.K.; Halimon, L.N.; Yeroshenko, G.A. (World of Medicine and Biology, 2014)
In Ukraine, the epidemic of tuberculosis. In order to detect infected, bend tuberculin tests, selection on the booster and diagnosis of post-vaccination and post-infectious allergies applies tuberculin diagnostics. At the present stage the Mantoux test with 2TE displaces Diaskintest or intracutaneous test with the allergen recombinant tuberculosis.
Keywords: tuberculinodiagnostic; Diaskintest